Magnetron sputtering coated glass and preparation process thereof
By using magnetron sputtering technology to set up a multi-layer film layer on the glass substrate, the problem of insufficient light transmittance of existing low-radiation glass is solved, and the coated glass with high transmittance and strong thermal insulation performance is achieved.
Patent Information
- Application Number
- CN202510135525.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-23
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-02-07
AI Technical Summary
The insufficient light transmittance of existing low-radiation glass products affects the natural lighting effect of the indoors, especially in time or area when there is insufficient light.
Magneto-controlled sputtering technology is used to stack and arrange multi-layer film layers on the glass substrate, including silicon nitride layer, titanium oxide layer, zinc aluminum oxide layer, metal silver layer, metal titanium layer and silicon oxide doped layer, to form a low-radiation film system to improve light transmittance and thermal insulation performance.
High transmittance to visible light and high reflectance to infrared light are achieved, improving the thermal insulation performance and natural lighting effect of glass.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-radiation glass, in particular to magnetron sputtering coated glass and a preparation process thereof. Background Art
[0002] Coated glass, also known as reflective glass, is coated with one or more layers of metal, alloy or metal compound film on the surface of the glass to change the optical properties of the glass to meet certain specific requirements. According to the product characteristics, it can be divided into heat reflective glass, low-emissivity (LOW-E) glass, conductive film glass, etc. The most commonly used coated glass is heat reflective glass and low-emissivity glass. Basically, two production methods are used: vacuum magnetron sputtering and chemical vapor deposition.
[0003] Among them, heat-reflective glass is generally coated with one or more layers of metal chromium, metal titanium or stainless steel or other metals or their compounds on the glass surface, which has a proper transmittance to visible light, a high reflectivity to infrared light, and a high absorption rate to ultraviolet light. Therefore, it is also called sunlight control glass, which is mainly used in the fields of building curtain walls, glass curtain walls, etc.
[0004] Low-emissivity glass is a glass surface coated with multiple layers of metals such as silver, copper or tin or their compounds. It has a high transmittance to visible light and a high reflectivity to infrared light, which makes it have good heat insulation performance and is mainly used in buildings, automobiles, and ships. However, some existing low-emissivity glass products have insufficient light transmittance, which affects the natural lighting effect of the room behind the glass, especially in times or areas with insufficient light, causing the indoor light to be dim. Therefore, we propose magnetron sputtering coated glass and its preparation process. Summary of the invention
[0005] The object of the present invention is to provide magnetron sputtering coated glass and a preparation process thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solution: magnetron sputtering coated glass comprises a glass substrate, and a dielectric film, an interface film and a metal film are arranged on the upper surface of the glass substrate.
[0007] Furthermore, the dielectric film is a metal oxide or silicon nitride, silicon zirconium nitride, and the metal oxide includes but is not limited to one or more of titanium oxide, silicon oxide, vanadium oxide, nickel chromium oxide, zirconium oxide, zinc oxide, zinc aluminum oxide, zinc tin oxide, bismuth oxide, tin oxide, indium tin oxide, cobalt oxide, niobium oxide, cadmium oxide, and indium oxide.
[0008] Furthermore, the interface film includes, but is not limited to, one or more of zinc oxide, zinc aluminum oxide, titanium oxide, nickel chromium oxide, nickel chromium, metal titanium, and indium tin oxide.
[0009] Furthermore, the metal film includes but is not limited to one or more of silver, copper, gold, and aluminum.
[0010] Furthermore, the upper surface of the glass substrate is stacked with the following film layers from bottom to top: the first film layer is a silicon nitride layer with a thickness of 15 to 25 nm; silicon nitride has excellent acid and alkali resistance and scratch resistance, and can block the diffusion of impurities when plated on the surface of the glass substrate, preventing the diffusion of ions in the glass substrate and avoiding affecting the film layer properties. However, the affinity between silicon nitride and the metal silver layer is very poor, and an interface layer needs to be added between the two.
[0011] The second film layer is a titanium oxide layer with a thickness of 20 to 30 nm. The titanium oxide layer is added to the surface of the silicon nitride layer to form a composite film layer, which can coordinate its mechanical properties and thermal stability, protect the glass substrate, and enable the produced coated glass to have more excellent comprehensive performance.
[0012] The third film layer is a zinc oxide aluminum layer with a thickness of 5 to 10 nm. Zinc oxide has a smooth characteristic, and the zinc oxide aluminum layer (AZO) is zinc oxide doped with aluminum, which not only has the characteristics of a smooth surface and a dense structure, but also has a high refractive index and good sputtering efficiency, which can make the silver layer plated thereon more uniform. As a seed layer of the metallic silver layer, it has a good growth condition and better comprehensive performance. It can reduce the reflectivity of the metallic silver layer, enhance the visible light transmittance and emissivity of the film system, and improve its thermal insulation performance.
[0013] The fourth film layer is a metallic silver layer with a thickness of 8 to 10 nm. Silver is one of the substances with the lowest emissivity in nature. Plating a silver layer on the surface of glass can effectively reduce the emissivity of the glass and achieve high reflection of infrared light. The nano-scale silver layer allows visible light to pass through and has relatively low absorption of visible light, giving it good spectral transmission and reflection characteristics. However, the chemical and thermal properties of the metallic silver layer are unstable, and its performance will deteriorate under thermal oxidation and corrosion.
[0014] The fifth film layer is a metal titanium layer with a thickness of 1 to 3 nm. The titanium layer is provided as a stable barrier layer to protect the metal silver layer from the invasion of oxygen and other pollutants in subsequent processes, and to improve the adhesion between the silver layer and the dielectric layer. The composite of the metal silver layer and the titanium layer and the control of their thickness can help the produced coated glass to maintain its transmittance to visible light while improving its reflective performance for infrared light, thereby improving its heat insulation effect.
[0015] The sixth film layer is a titanium oxide layer with a thickness of 8 to 15 nm. Titanium oxide has good acid and alkali resistance and has a good effect of blocking the diffusion of impurities. It has good adhesion with the silver layer plated with metal titanium. It has good surface wettability, can relieve interface stress, and improve connection strength. At the same time, it has a good refractive index, can improve light transmittance, and is suitable as a dielectric film. However, due to its high refractive index, a slight change in the thickness of the titanium oxide layer caused by scratches will have a large optical impact. Therefore, the titanium oxide layer is not suitable as the top dielectric film of coated glass.
[0016] The seventh film layer is a zinc-aluminum oxide layer with a thickness of 5 to 10 nm;
[0017] The eighth film layer is a metallic silver layer with a thickness of 6 to 12 nm;
[0018] The ninth film layer is a metal titanium layer with a thickness of 1 to 3 nm;
[0019] The tenth film layer is a titanium oxide layer with a thickness of 20 to 30 nm;
[0020] The eleventh film layer is a zinc-aluminum oxide layer with a thickness of 5 to 10 nm;
[0021] The twelfth film layer is a metallic silver layer with a thickness of 5 to 13 nm. The coated glass in the present application is provided with three silver layers, which has an extremely low surface emissivity and a stronger heat energy blocking effect compared with double silver and single silver.
[0022] The thirteenth film layer is a metal titanium layer with a thickness of 1 to 3 nm;
[0023] The fourteenth film layer is a titanium oxide layer with a thickness of 20 to 30 nm;
[0024] The fifteenth film layer is a zinc oxide silicon layer with a thickness of 10 to 20 nm;
[0025] The sixteenth film layer is silicon nitride with a thickness of 8 to 15 nm. Silicon doped with zinc oxide can enhance the strength and stability of the film layer, and cooperate with the outermost protective layer (the sixteenth film layer) to improve the scratch resistance, wear resistance, and chemical resistance of the film layer on the surface of the coated glass; it can also increase the reflection and scattering of ultraviolet rays by the film layer, and improve the thermal insulation performance of the coated glass.
[0026] The preparation process of magnetron sputtering coated glass includes the following process steps:
[0027] (1) using argon as working gas, nitrogen as reaction gas, and silicon as target material, DC magnetron sputtering is performed to deposit and form a silicon nitride layer; the sputtering power is 100-120 W, the gas pressure is 0.005-0.008 mbar, and the ratio of argon to nitrogen is 1:(1.4-1.6);
[0028] (2) using argon as the working gas and titanium dioxide as the target material, DC magnetron sputtering is performed to deposit and form a titanium oxide layer; the sputtering power is 150 to 200 W, and the gas pressure is 0.003 to 0.005 mbar;
[0029] (3) using argon as the working gas and zinc aluminum oxide as the target material, DC magnetron sputtering is performed to deposit and form a zinc aluminum oxide layer; the sputtering power is 80 to 100 W, and the gas pressure is 0.003 to 0.005 mbar;
[0030] (4) using argon as the working gas and silver as the target material, performing AC magnetron sputtering to deposit and form a metallic silver layer; the sputtering power is 70 to 90 W, and the gas pressure is 0.002 to 0.003 mbar;
[0031] (5) using argon as the working gas, hydrogen as the reaction gas, and titanium as the target material, performing AC magnetron sputtering to deposit and form a metal titanium layer; the sputtering power is 45 to 55 W, the gas pressure is 0.002 to 0.004 mbar, and the ratio of argon to nitrogen is 1:(0.1 to 0.5);
[0032] Titanium is used as a target material for magnetron sputtering, and a metallic titanium layer is deposited. While serving as a barrier layer for the metallic silver layer, hydrogen is introduced into the titanium layer lattice during the magnetron sputtering process to form an unsaturated TiHx film layer, making it more metallic, reducing the real part of infrared light and increasing the imaginary part, while the change in visible light is not significant, which increases the glass's absorption of infrared light and propagates more slowly, and can significantly reduce infrared light radiation, thereby improving the thermal insulation capacity of the coated glass. Compared with acid-etched hydrogenated and saturated hydrogenated titanium, it has relatively higher strength and better morphology, and has better bonding ability with the titanium oxide layer set on its surface, and the overall strength of the produced coated glass is improved.
[0033] (6) using argon as the working gas and titanium dioxide as the target material, DC magnetron sputtering is performed to deposit and form a titanium oxide layer; the sputtering power is 150 to 200 W, and the gas pressure is 0.003 to 0.005 mbar;
[0034] The titanium oxide film is relatively stable and can serve as an effective barrier to hydrogen penetration. It also has good heat resistance and can alleviate the thermal effects caused by the strong near-infrared absorption ability of the metal titanium layer.
[0035] (7) repeating steps (3) to (6) twice to sequentially form a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer, a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer;
[0036] (8) Using argon as the working gas and zinc oxide silicon as the target material, DC magnetron sputtering is performed to deposit and form a zinc oxide silicon layer; the sputtering power is 80 to 120 W, and the gas pressure is 0.003 to 0.005 mbar;
[0037] (9) using argon as the working gas, nitrogen as the reaction gas, and silicon as the target material, performing DC magnetron sputtering to deposit and form a silicon nitride layer;
[0038] The sputtering power is 100-120W, the gas pressure is 0.005-0.008mbar, and the ratio of argon to nitrogen is 1:(1.4-1.6) to obtain coated glass.
[0039] Furthermore, step (6) can be replaced by the following process:
[0040] Using argon as working gas, trifluoromethane as reaction gas, and composite silicon dioxide as target material, direct current magnetron sputtering is performed to deposit and form a silicon oxide doped layer;
[0041] The sputtering power is 50-70 W, the gas pressure is 0.018-0.025 mbar, and the ratio of argon to trifluoromethane is 1:(0.4-0.6).
[0042] Furthermore, the target material, composite silicon dioxide is prepared by the following process:
[0043] Mixing ethyl orthosilicate, ethanol and ammonium fluoride, adjusting the pH to 3.5-4.5 with hydrochloric acid, and standing for hydrolysis for 8-24 hours to obtain a glue solution;
[0044] The silicon dioxide and graphite are ball-milled, and a hydrolyzate is added and mixed to prepare a mixture; and the mixture is hot-pressed and sintered to obtain composite silicon dioxide.
[0045] Further, the mixture includes the following components by mass: 20 to 35 parts of graphite, 65 to 80 parts of silicon dioxide and 10 to 30 parts of glue;
[0046] In the glue solution, the molar ratio of tetraethyl orthosilicate to ammonium fluoride is 10:(0.5-1.2);
[0047] The ratio of ethyl orthosilicate to ethanol is (1-3) g / 10 mL; the concentration of ethanol is 70-90 v %;
[0048] The concentration of hydrochloric acid is 1M.
[0049] Furthermore, the process conditions of hot pressing sintering are: evacuate to below 100Pa, heat up to 150-180°C, keep warm for 30-60min; heat up to 660-700°C, keep warm for 60-90min; heat up to 750-820°C, keep warm for 60-90min; pressurize to 20-30MPa, keep warm and pressure for 90-120min.
[0050] In the above technical scheme, the hydrolysis of tetraethyl orthosilicate in ethanol is used to form a glue, and silicon dioxide and graphite are mixed, and the target material is prepared after hot pressing and sintering. The glue contains ammonium fluoride, and the radius of its fluoride ion is similar to that of the hydroxyl ion, so that Si-OH produced by the hydrolysis of tetraethyl orthosilicate is easy to undergo substitution reaction with ammonium fluoride, so that more fluoride ions exist in the form of HF, and overflow at the high temperature of hot pressing and sintering, catalyzing the hydrolysis and polymerization of tetraethyl orthosilicate, reducing the content of hydroxyl and water in the glue, promoting the compound between silicon dioxide and graphite particles, reducing target material defects, and being conducive to the uniformity and stability of the performance of the prepared target material. Some fluoride ions enter the network to form Si-F bonds during the sintering process, which helps to increase the fluorine content in the prepared silicon oxide doping layer and improve its optical properties.
[0051] The silicon dioxide target contains graphite, which can be deposited to form a fluorine-containing diamond-like structure under the action of magnetron sputtering and gas source trifluoromethane, so that the formed film layer is a diamond-like composite film layer of silicon dioxide doped with fluorine, which is recorded as a silicon oxide doped layer. Compared with titanium dioxide, it has a wider band gap width, a relatively lower refractive index and a higher infrared reflection and absorption ability.
[0052] In the above technical solution, the hydrogenation of the metal titanium layer increases the real part of the ultraviolet light, which promotes the faster propagation of ultraviolet light in the glass. Compared with titanium oxide, the silicon oxide doping layer can increase the absorption, reflection and scattering of ultraviolet light by the coated glass, reduce the irradiation of ultraviolet light, and make it have good radiation resistance.
[0053] The silicon oxide doped layer has better infrared light reflection and absorption performance, and has good high temperature resistance, which can effectively reduce the heat conduction in the coated glass, thereby improving the heat insulation capacity of the coated glass. Its band gap width is relatively wider, the absorption of light is weakened, and it has higher visible light transmittance. It can also improve the refractive uniformity of the metal titanium layer, ensure optical stability, and improve the stability and uniformity of the optical properties of the coated glass.
[0054] The silicon oxide doped layer has a uniform and high refractive index, which ensures the stability of the optical performance of the coated glass. Compared with titanium dioxide, the refractive index of the silicon oxide doped layer is lower, lower than the refractive index of the adjacent metal film layer, and higher than the refractive index of zinc oxide silicon, thus forming a film layer system with a step-by-step and cyclic refractive index (metal silver layer-metal titanium layer-silicon oxide doped layer-zinc oxide aluminum layer), which reduces the reflection and scattering of light, improves the transmission efficiency of visible light, reduces the refractive index difference between film layers, alleviates the reflection and refraction of visible light between film layers, reduces reflection loss, and further improves the transmittance of visible light.
[0055] The sputtering deposition of the silicon dioxide doped layer can bind the fluorine free radicals in the fluorine-doped silicon oxide glass to prevent the adjacent film layers from being corroded; it can also serve as a barrier to hydrogen penetration, blocking the hydrogenation of the metal titanium layer to meet the design requirements of the coated glass.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] 1. The magnetron sputtering coated glass and its preparation process described in the present invention form a low-radiation film system by depositing multiple layers of dielectric films, interface films and metal films on the surface of a glass substrate using magnetron sputtering, thereby achieving the transmission of visible light and reflection of infrared light by the coated glass.
[0058] 2. The magnetron sputtering coated glass and its preparation process described in the present invention increase the absorption of infrared light by the glass and slow down the propagation of infrared light by arranging an unsaturated hydrogenated metal titanium layer on the surface of the metal silver layer, which can greatly reduce the radiation of infrared light and improve the heat insulation capacity of the coated glass.
[0059] 3. The magnetron sputtering coated glass and its preparation process described in the present invention, by setting a silicon oxide doping layer on the surface of the metal titanium layer, doped with a diamond-like composite film layer and fluorine, has a wider band gap width, a relatively lower refractive index and a higher infrared reflection and absorption ability, further improving the light transmittance and heat insulation ability of the coated glass. DETAILED DESCRIPTION
[0060] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] In the following specific implementations,
[0062] The glass substrate is soda-lime glass with a thickness of 1.2 mm, which is sourced from Sinopharm Chemical Reagent Co., Ltd.;
[0063] Silicon dioxide: RDB-BC-SiO2, purity 4N, from Shanghai Yanbei New Material Technology Co., Ltd.;
[0064] Graphite: purity 99.98%, particle size 3-10μm, sourced from Qingdao Tianshengda Graphite Co., Ltd.
[0065] The purity of the gas is 99.995%;
[0066] Target materials: The purity of silicon, silver and titanium is 5N, and the purity of titanium dioxide is 4N, all of which are from Beijing Zhongjinyan New Materials Co., Ltd.;
[0067] Zinc oxide aluminum: purity 4N, Al doping amount w (Al2O3) is 2.0%, from Zhongnuo New Materials (Beijing) Technology Co., Ltd.;
[0068] Zinc oxide silicon: purity 4N, Si doping amount w (SiO2) is 25%, sourced from Jiangxi Ketai New Materials Co., Ltd.
[0069] Embodiment 1: A process for preparing magnetron sputtering coated glass, comprising the following process steps:
[0070] (1) using argon as working gas, nitrogen as reaction gas, and silicon as target material, DC magnetron sputtering was performed to deposit a silicon nitride layer with a thickness of 15 nm; the sputtering power was 100 W, the gas pressure was 0.005 mbar, and the ratio of argon to nitrogen was 1:1.4;
[0071] (2) Using argon as the working gas and titanium dioxide as the target, DC magnetron sputtering was performed to deposit a titanium oxide layer with a thickness of 20 nm; the sputtering power was 150 W and the gas pressure was 0.003 mbar;
[0072] (3) Using argon as the working gas and zinc aluminum oxide as the target material, DC magnetron sputtering was performed to deposit a zinc aluminum oxide layer with a thickness of 5 nm; the sputtering power was 80 W and the gas pressure was 0.003 mbar;
[0073] (4) using argon as the working gas and silver as the target material, AC magnetron sputtering was performed to deposit a metallic silver layer with a thickness of 8 nm; the sputtering power was 70 W and the gas pressure was 0.002 mbar;
[0074] (5) using argon as the working gas, hydrogen as the reaction gas, and titanium as the target material, AC magnetron sputtering was performed to deposit a metal titanium layer with a thickness of 1 nm; the sputtering power was 45 W, the gas pressure was 0.002 mbar, and the ratio of argon to nitrogen was 1:0.1;
[0075] (6) Mixing tetraethyl orthosilicate, 70% by volume ethanol and ammonium fluoride, adjusting the pH to 3.5 with 1M hydrochloric acid, and allowing to stand for hydrolysis for 8 hours to obtain a glue solution; the molar ratio of tetraethyl orthosilicate to ammonium fluoride is 10:0.5; the ratio of tetraethyl orthosilicate to ethanol is 1 g / 10 mL;
[0076] The silicon dioxide and graphite are ball-milled, and the hydrolyzate is added and mixed to prepare a mixture; the mixture is hot-pressed and sintered, and the process is as follows: vacuuming to below 100Pa, heating to 150°C, and keeping the temperature for 30min; heating to 660°C, and keeping the temperature for 60min; heating to 750°C, and keeping the temperature for 60min; pressurizing to 20MPa, and keeping the temperature and pressure for 120min to obtain composite silicon dioxide; the mixture includes the following mass components: 20 parts of graphite, 80 parts of silicon dioxide and 10 parts of glue;
[0077] Using argon as the working gas, trifluoromethane as the reaction gas, and composite silicon dioxide as the target material, DC magnetron sputtering was performed to deposit and form a silicon oxide doped layer; the sputtering power was 50W, the gas pressure was 0.018mbar, and the ratio of argon to trifluoromethane was 1:0.4;
[0078] (7) repeating steps (3) to (6) twice to sequentially form a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer, a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer;
[0079] (8) Using argon as the working gas and zinc oxide silicon as the target material, DC magnetron sputtering is performed to deposit a zinc oxide silicon layer with a thickness of 10 nm; the sputtering power is 80 W and the gas pressure is 0.003 mbar;
[0080] (9) Using argon as the working gas, nitrogen as the reaction gas, and silicon as the target material, direct current magnetron sputtering is performed to deposit a silicon nitride layer with a thickness of 8 μm; the sputtering power is 100 W, the gas pressure is 0.005 mbar, and the ratio of argon to nitrogen is 1:1.4 to obtain coated glass.
[0081] Embodiment 2: A process for preparing magnetron sputtering coated glass, comprising the following process steps:
[0082] (1) Using argon as the working gas, nitrogen as the reaction gas, and silicon as the target, direct current magnetron sputtering was performed to deposit a silicon nitride layer with a thickness of 20 nm; the sputtering power was 110 W, the gas pressure was 0.006 mbar, and the ratio of argon to nitrogen was 1:1.5;
[0083] (2) Using argon as the working gas and titanium dioxide as the target, DC magnetron sputtering was performed to deposit a titanium oxide layer with a thickness of 25 nm; the sputtering power was 180 W and the gas pressure was 0.004 mbar;
[0084] (3) Using argon as the working gas and zinc aluminum oxide as the target, DC magnetron sputtering was performed to deposit a zinc aluminum oxide layer with a thickness of 8 nm; the sputtering power was 90 W and the gas pressure was 0.004 mbar;
[0085] (4) using argon as the working gas and silver as the target material, AC magnetron sputtering was performed to deposit a metal silver layer with a thickness of 9 nm; the sputtering power was 80 W and the gas pressure was 0.002 mbar;
[0086] (5) using argon as the working gas, hydrogen as the reaction gas, and titanium as the target material, AC magnetron sputtering was performed to deposit a metal titanium layer with a thickness of 2 nm; the sputtering power was 50 W, the gas pressure was 0.003 mbar, and the ratio of argon to nitrogen was 1:0.3;
[0087] (6) Mixing tetraethyl orthosilicate, 80% by volume ethanol and ammonium fluoride, adjusting the pH to 4 with 1M hydrochloric acid, and allowing to stand for hydrolysis for 16 hours to obtain a glue solution; the molar ratio of tetraethyl orthosilicate to ammonium fluoride is 10:0.8; the ratio of tetraethyl orthosilicate to ethanol is 2 g / 10 mL;
[0088] The silicon dioxide and graphite are ball-milled, and the hydrolyzate is added and mixed to prepare a mixture; the mixture is hot-pressed and sintered, and the process is as follows: evacuate to below 100Pa, heat up to 165°C, and keep the temperature for 45min; heat up to 680°C, and keep the temperature for 75min; heat up to 785°C, and keep the temperature for 75min; pressurize to 25MPa, and keep the temperature and pressure for 105min to obtain composite silicon dioxide; the mixture includes the following mass components: 28 parts of graphite, 72 parts of silicon dioxide and 20 parts of glue;
[0089] Using argon as the working gas, trifluoromethane as the reaction gas, and composite silicon dioxide as the target material, DC magnetron sputtering was performed to deposit and form a silicon oxide doped layer; the sputtering power was 60W, the gas pressure was 0.021mbar, and the ratio of argon to trifluoromethane was 1:0.5;
[0090] (7) repeating steps (3) to (6) twice to sequentially form a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer, a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer;
[0091] (8) Using argon as the working gas and zinc oxide silicon as the target material, DC magnetron sputtering is performed to deposit a zinc oxide silicon layer with a thickness of 15 nm; the sputtering power is 100 W and the gas pressure is 0.004 mbar;
[0092] (9) Using argon as the working gas, nitrogen as the reaction gas, and silicon as the target, direct current magnetron sputtering is performed to deposit a silicon nitride layer with a thickness of 12 nm; the sputtering power is 110 W, the gas pressure is 0.006 mbar, and the ratio of argon to nitrogen is 1:1.5 to obtain coated glass.
[0093] Embodiment 3: A process for preparing magnetron sputtering coated glass, comprising the following process steps:
[0094] (1) using argon as working gas, nitrogen as reaction gas, and silicon as target material, DC magnetron sputtering was performed to deposit a silicon nitride layer with a thickness of 25 nm; the sputtering power was 120 W, the gas pressure was 0.008 mbar, and the ratio of argon to nitrogen was 1:1.6;
[0095] (2) Using argon as the working gas and titanium dioxide as the target, DC magnetron sputtering was performed to deposit a titanium oxide layer with a thickness of 30 nm; the sputtering power was 200 W and the gas pressure was 0.005 mbar;
[0096] (3) Using argon as the working gas and zinc aluminum oxide as the target material, DC magnetron sputtering was performed to deposit a zinc aluminum oxide layer with a thickness of 10 nm; the sputtering power was 100 W and the gas pressure was 0.005 mbar;
[0097] (4) using argon as the working gas and silver as the target material, AC magnetron sputtering was performed to deposit a metal silver layer with a thickness of 10 nm; the sputtering power was 90 W and the gas pressure was 0.003 mbar;
[0098] (5) using argon as the working gas, hydrogen as the reaction gas, and titanium as the target material, AC magnetron sputtering was performed to deposit a metal titanium layer with a thickness of 3 nm; the sputtering power was 55 W, the gas pressure was 0.004 mbar, and the ratio of argon to nitrogen was 1:0.5;
[0099] (6) Mixing tetraethyl orthosilicate, 90% by volume ethanol and ammonium fluoride, adjusting the pH to 4.5 with 1M hydrochloric acid, and allowing to stand for hydrolysis for 24 hours to obtain a glue solution; the molar ratio of tetraethyl orthosilicate to ammonium fluoride is 10:1.2; the ratio of tetraethyl orthosilicate to ethanol is 3 g / 10 mL;
[0100] The silicon dioxide and graphite are ball-milled, and the hydrolyzate is added and mixed to prepare a mixture; the mixture is hot-pressed and sintered, and the process is as follows: vacuuming to below 100Pa, heating to 180°C, and keeping the temperature for 60min; heating to 700°C, and keeping the temperature for 90min; heating to 820°C, and keeping the temperature for 90min; pressurizing to 30MPa, and keeping the temperature and pressure for 120min to obtain composite silicon dioxide; the mixture includes the following mass components: 35 parts of graphite, 65 parts of silicon dioxide and 30 parts of glue;
[0101] Using argon as the working gas, trifluoromethane as the reaction gas, and composite silicon dioxide as the target material, DC magnetron sputtering was performed to deposit and form a silicon oxide doped layer; the sputtering power was 70W, the gas pressure was 0.025mbar, and the ratio of argon to trifluoromethane was 1:0.6;
[0102] (7) repeating steps (3) to (6) twice to sequentially form a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer, a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer;
[0103] (8) Using argon as the working gas and zinc oxide silicon as the target material, DC magnetron sputtering is performed to deposit a zinc oxide silicon layer with a thickness of 20 nm; the sputtering power is 120 W and the gas pressure is 0.005 mbar;
[0104] (9) Using argon as the working gas, nitrogen as the reaction gas, and silicon as the target, direct current magnetron sputtering is performed to deposit a silicon nitride layer with a thickness of 15 nm; the sputtering power is 120 W, the gas pressure is 0.008 mbar, and the ratio of argon to nitrogen is 1:1.6 to obtain coated glass.
[0105] Comparative Example 1: A process for preparing magnetron sputtering coated glass, comprising the following process steps:
[0106] (6) Using argon as the working gas and titanium dioxide as the target, DC magnetron sputtering was performed to deposit a titanium oxide layer with a thickness of 8 nm; the sputtering power was 150 W and the gas pressure was 0.003 mbar;
[0107] Steps (1-4) and (7-9) are the same as those in Example 1 to obtain coated glass.
[0108] Experiment: Take the coated glass obtained in Examples 1-3 and Comparative Example 1, prepare samples, test their properties respectively and record the test results:
[0109] Use a UV-visible spectrometer to detect the transmittance of the coated glass sample in the wavelength range of 380nm-800nm;
[0110] The infrared reflectivity R of the coated glass sample was detected by Fourier infrared spectrometer, and its emissivity (1-R) was calculated;
[0111] A thermal conductivity meter was used to test the thermal conductivity of the coated glass samples.
[0112] Visible light transmittance (%) Emissivity Thermal conductivity (W / m·K) Example 1 89.2 0.34 0.63 Example 2 91.4 0.30 0.50 Example 3 87.7 0.27 0.45 Comparative Example 1 79.8 0.42 1.23
[0113] According to the data in the above table, we can clearly draw the following conclusions:
[0114] The coated glass obtained in Examples 1-3 is compared with the coated glass obtained in Comparative Example 1. The test results show that:
[0115] Compared with the comparative example, the coated glass obtained in Examples 1-3 has higher visible light transmittance and lower emissivity and thermal conductivity data, which fully demonstrates that the present invention achieves improvement in the light transmittance and heat insulation capabilities of the prepared coated glass.
[0116] Similar to Example 1, Comparative Example 1 replaces the silicon oxide doped layer with a titanium dioxide layer. Its visible light transmittance is low, and its emissivity and thermal conductivity data are high. It can be seen that the arrangement of the coated glass film layer and its process of the present invention can promote the improvement of its light transmission and heat insulation capabilities.
[0117] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. Magnetron sputtering coated glass, characterized by: The invention comprises a glass substrate, wherein the upper surface of the glass substrate is provided with the following film layers stacked in sequence from bottom to top: a first film layer of a silicon nitride layer, a second film layer of a titanium oxide layer, a third film layer of a zinc aluminum oxide layer, a fourth film layer of a metal silver layer, a fifth film layer of a metal titanium layer, a sixth film layer of a titanium oxide layer, a seventh film layer of a zinc aluminum oxide layer, an eighth film layer of a metal silver layer, a ninth film layer of a metal titanium layer, a tenth film layer of a titanium oxide layer, an eleventh film layer of a zinc aluminum oxide layer, a twelfth film layer of a metal silver layer, a thirteenth film layer of a metal titanium layer, a fourteenth film layer of a titanium oxide layer, a fifteenth film layer of a zinc silicon oxide layer, and a sixteenth film layer of a silicon nitride layer.
2. The process for preparing magnetron sputtering coated glass according to claim 1, characterized in that: The process steps include: (1) using argon as working gas, nitrogen as reaction gas, and silicon as target material, DC magnetron sputtering is performed to deposit and form a silicon nitride layer; (2) using argon as the working gas and titanium dioxide as the target material, DC magnetron sputtering is performed to deposit and form a titanium oxide layer; (3) using argon as the working gas and zinc aluminum oxide as the target material, DC magnetron sputtering is performed to deposit and form a zinc aluminum oxide layer; (4) using argon as the working gas and silver as the target material, performing AC magnetron sputtering to deposit and form a metallic silver layer; (5) using argon as the working gas, hydrogen as the reaction gas, and titanium as the target material, performing AC magnetron sputtering to deposit and form a metal titanium layer; (6) using argon as the working gas and titanium dioxide as the target material, performing DC magnetron sputtering to deposit and form a titanium oxide layer; (7) repeating steps (3) to (6) twice to sequentially form a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer, a zinc oxide aluminum layer, a metal silver layer, a metal titanium layer and a titanium oxide layer; (8) using argon as the working gas and zinc oxide silicon as the target material, performing DC magnetron sputtering to deposit and form a zinc oxide silicon layer; (9) Using argon as the working gas, nitrogen as the reaction gas, and silicon as the target material, direct current magnetron sputtering is performed to deposit and form a silicon nitride layer to obtain coated glass.
3. The process for preparing magnetron sputtering coated glass according to claim 1, characterized in that: In step (1), the sputtering power is 100-120 W, the gas pressure is 0.005-0.008 mbar, and the ratio of argon to nitrogen is 1:(1.4-1.6); In step (2), the sputtering power is 150-200 W and the gas pressure is 0.003-0.005 mbar; In step (3), the sputtering power is 80-100 W and the gas pressure is 0.003-0.005 mbar; In step (4), the sputtering power is 70-90 W, and the gas pressure is 0.002-0.003 mbar.
4. The process for preparing magnetron sputtering coated glass according to claim 1, characterized in that: In step (5), the sputtering power is 45-55 W, the gas pressure is 0.002-0.004 mbar, and the ratio of argon to nitrogen is 1:(0.1-0.5); In step (6), the sputtering power is 150-200 W, and the gas pressure is 0.003-0.005 mbar; In step (8), the sputtering power is 80-120 W and the gas pressure is 0.003-0.005 mbar; In step (9), the sputtering power is 100-120 W, the gas pressure is 0.005-0.008 mbar, and the ratio of argon to nitrogen is 1:(1.4-1.6).
5. The process for preparing magnetron sputtering coated glass according to claim 1, characterized in that: Step (6) can be replaced by the following process: With argon as working gas, trifluoromethane as reaction gas and composite silicon dioxide as target material, direct current magnetron sputtering is performed to deposit and form a silicon oxide doped layer.
6. The process for preparing magnetron sputtering coated glass according to claim 5, characterized in that: The process conditions of magnetron sputtering are: sputtering power 50-70 W, gas pressure 0.018-0.025 mbar, and the ratio of argon to trifluoromethane is 1:(0.4-0.6).
7. The process for preparing magnetron sputtering coated glass according to claim 5, characterized in that: The target material, composite silicon dioxide is prepared by the following process: Mixing ethyl orthosilicate, ethanol and ammonium fluoride, adjusting the pH to 3.5-4.5 with hydrochloric acid, and standing for hydrolysis for 8-24 hours to obtain a glue solution; The silicon dioxide and graphite are ball-milled, and a hydrolyzate is added and mixed to prepare a mixture; and the mixture is hot-pressed and sintered to obtain composite silicon dioxide.
8. The process for preparing magnetron sputtering coated glass according to claim 7, characterized in that: The mixture comprises the following components by weight: 20 to 35 parts of graphite, 65 to 80 parts of silicon dioxide and 10 to 30 parts of glue.
9. The process for preparing magnetron sputtering coated glass according to claim 7, characterized in that: In the glue solution, the molar ratio of tetraethyl orthosilicate to ammonium fluoride is 10:(0.5-1.2).
10. The process for preparing magnetron sputtering coated glass according to claim 7, characterized in that: The process conditions of hot pressing sintering are: vacuuming, heating to 150-180°C, keeping warm for 30-60 minutes; heating to 660-700°C, keeping warm for 60-90 minutes; heating to 750-820°C, keeping warm for 60-90 minutes; pressurizing to 20-30MPa, keeping warm and pressure for 90-120 minutes.
Citation Information
Patent Citations
Sapphire three-silver low-emissivity coated glass with high light heat ratio
CN107777899A
High-transmittance neutral-color temperable double-silver low-emissivity coated glass and preparation method thereof
CN116535106A
Titania-doped quartz glass and making method
US20120058419A1
Cited By
High-stability ITO conductive glass and preparation method thereof
CN120328874A